PENGARUH MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE JIGSAW TERHADAP PENINGKATAN HASIL BELAJAR SISWA KELAS VIII DI SMP SWASTA KARYA KASIH ZUZUNDRAO KECAMATAN MANDREHE KABUPATEN NIAS BARAT - Gulo, Nurli Berkat (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2025)
This research was motivated by the increase in student learning outcomes in class VIII of SMP Swasta Karya Kasih Zuzundrao, that the increase in learning outcomes of students who were less active in learning was caused by the learning model used. The aim of this research is to determine the improvement in student learning outcomes through the influence of the Jigsaw Type Quasi Cooperative Learning model. This research method is experimental using quantitative research. The instruments used are learning outcomes tests and documentation. The samples used in this research were class VIII-a with 28 students as the experimental class and class VIII-b with 25 students as the control class. Based on the calculation of the hypothesis results, the calculated tcount was obtained, > ttable (0.027> 0.05). This shows that the value of tcount>ttable means that Ha is accepted and Ho is rejected, which means that there is an influence of the Jigsaw Type Cooperative Learning model on improving student learning outcomes. So it can be concluded that students are able to achieve mastery of the Jigsaw Type Cooperative Learning approach to learning approaches that require students to completely master all competency standards and basic competencies in certain subjects individually or in groups: (1) the teacher wants to apply the Jigsaw Type Cooperative Learning Model competency standards and basic competencies in economic subjects can be implemented systematically so that students master them completely; (2) The results of this research should be used as comparison material for other researchers.